Effects of Shenling Baizhu powder on intestinal microflora metabolites and liver mitochondrial energy metabolism in nonalcoholic fatty liver mice - Yao, Zheng; Guo, Jia; Du, Bing; Hong, Li; Zhu, Ying; Feng, Xiaoyi; Hou, Yuanlu; Shi, Anhua (Frontiers in Microbiology, 2023)
Background & Purpose: Non-alcoholic fatty liver disease (NAFLD) is characterised by the excessive accumulation of triglycerides in the liver. Shenling Baizhu powder (SLBZP) is formulated from various natural medicinal plants that protect the liver and are used to treat intestinal diseases. SLBZP improves the symptoms of NAFLD. However, its mechanism of action remains unclear. Herein, we investigated the ameliorative effect of SLBZP on model mice with high-fat-diet (HFD)-induced NAFLD. Additionally, we evaluated the impact of SLBZP on the intestinal flora and its metabolites and mitochondrial energy metabolism in NAFLD. Methods: We used HFD to establish a mouse model of NAFLD. Different drug interventions were administered. We measured serum biochemical indices. Liver sections were visualised with hematoxylin–eosin and oil red O staining. 16S rDNA amplicon sequencing technology was used to analyse the diversity and abundance of the intestinal flora. Short-chain fatty acids (SCFAs) in the intestinal contents were detected using GC-MS. Liver tissue was sampled to detect mitochondrial membrane functional indices. Western blotting was used to determine the levels of mitochondrial pathway-related proteins, namely, uncoupling protein 2 (UCP2), adenosine monophosphate-activated protein kinase (AMPK) and inhibitory factor 1 (IF1) of F1Fo ATP synthesis/hydrolase, in the liver. Results: The spleen-invigorating classic recipe of SLBZP reduced liver lipid deposition in mice with HFD-induced NAFLD. Additionally, SCFAs produced by intestinal flora metabolism regulated the UCP2/AMPK/IF1 signalling pathway involved in liver mitochondrial energy metabolism to improve the liver mitochondrial membrane permeability, respiratory state and oxidative phosphorylation efficiency of mice with NAFLD. Finally, SLBZP increased the liver ATP level. Conclusion: Our results suggest that the therapeutic effect of SLBZP on NAFLD is related to the regulation of hepatic mitochondrial energy metabolism by intestinal flora and its metabolites and is possibly associated with the UCP2/AMPK/IF1 signalling pathway.